USE OF DAIRY INDUSTRY EFFLUENTS AND WASTE BEER YEAST FOR THE PRODUCTION OF YEAST EXTRACT AND ACETIC ACID - Flores P., A. (2009)
This work was carried out with the purpose to optimize physical chemical parameters obtain a microbial biomass from Kluyveromyces marxianus NRRL-Y-1109 and Saccharomyces cerevisiae. The yeasts were grown on sweet whey deproteinized, supplemented with nitrogen and vitamins sources and mollasses as carbon source far S. cerevísíae. The fermentation parameters were: An pH 4.5; Temperature 30ºC and an aeration rate of 1.75 VVM; Agitation speed 600 RPM, Lactase concentration 5 gi ; (NHJ2S04 6 g/L; Yeast extract 1.5 g/L . The average biomass yield obtained was 0.56 g/g lactase far K. marxianus and 0.46 g/g S. Cerevisae respectively grown on sweet whey deproteinized & molasses a cellular concentration of 12.75 g/L & 11.52 g/L respectively at the end of the fermentation. lt was obtained acetic acid (3.5 g/L) by aerobic fermentation of brewery liquid effluent.